Evaluating Government Spending on Climate Change Mitigation: Effects on Deforestation and Carbon Emissions in Kalimantan, Indonesia - Setiawan, Erik; Nuzul, Alief Ibnu; Taufan, Andy (Direktorat Sistem Perbendaharaan, 2025)
This study examines the impact of central and local government spending on deforestation and carbon emissions in Kalimantan, a region where emissions are predominantly driven by forest-related activities and fossil fuel consumption. Utilizing a panel data regression analysis from 2016 to 2022, the research considers central government spending and regional transfers as independent variables, with deforestation and carbon emissions as dependent variables, and controls for regional area, gross regional domestic product, and COVID-19 effects. The findings indicate that increased central government expenditure correlates with reduced deforestation, whereas local government spending shows no significant impact on deforestation. Additionally, central government spending is associated with higher carbon emissions, while regional transfers do not significantly affect carbon emissions. Efficiency analysis reveals that East Kalimantan is the most efficient province in reducing deforestation and carbon emissions, while Central, West, and North Kalimantan are the least efficient. The study suggests that budget refocusing is essential for more precise targeting to effectively reduce deforestation and carbon emissions. Furthermore, it highlights the necessity for enhanced coordination between central and local governments, particularly in Central, West, and North Kalimantan, to address climate change issues comprehensively. This research contributes to our understanding of the fiscal dynamics of environmental policy in Indonesia and provides insights for optimizing government spending to mitigate the impacts of climate change.